Heine, écrivain français putatif ? - Lucien Calvié (Recherches Germaniques)
Both during and after Heine’s lifetime, his French reception posed and re-posed the problem of his literary “nationality”: was he a “French writer” or “German poet”? The question also underlies the two major existing critical editions known as “Düsseldorfer Ausgabe” and “Weimarer Ausgabe”. Paradoxically, and even more than Germanistik in Germany, German Studies in France seem to have long favored, in various ways, a “German” Heine to the detriment of the “French” Heine. Perhaps it is time to have a more balanced approach to Heine, using for example the notion that Heine himself developed for one of his texts, of a “German book in the French language”. These considerations lead us to define Heine as a “putative French writer”, in addition to his lasting identity as a “German poet”.